IDEOLOGI DALAM STRUKTUR BAHASA: ANALISIS LINGUISTIK MODEL NORMAN FAIRCLOUGH PADA DEBAT KEABSAHAN IJAZAH JOKO WIDODO - Putri, Hesti Amelia; Yulianti, Uki Hares; Nugroho, Bivit Anggoro Prasetyo (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
The public debate over the legitimacy of Joko Widodo's diploma involves not only legal debates but also ideological content and linguistic strategies that reflect power relations in Indonesian politics. This study uses Norman Fairclough's Critical Discourse Analysis (CDA) approach to examine the micro-dimensions of language, specifically the aspects of cohesion, transitivity, modality, diction, and metaphor used in the debate. A descriptive qualitative method was applied with a focus on one episode of the debate on the iNews YouTube channel, using listening techniques and verbatim transcription. The results reveal that these five micro-linguistic aspects work synergistically in representing and reproducing ideologies that strengthen the position and dominance of power in political discourse. These findings provide a new contribution to the development of CDA, especially in the micro-level of Indonesian politics and emphasize the role of language as a tool of ideological struggle in public debate. The limited focus on one episode and micro-dimension is a limitation of this research, opening up opportunities for further study with a broader context and integration of macro-dimensions. The implications of this research are important for a critical understanding of language use in politics and social communication.